Exosomes of pasteurized milk: potential pathogens of Western diseases - Melnik, Bodo C. (J Transl Med, 2019)
Milk consumption is a hallmark of western diet. According to common believes, milk consumption has beneficial effects for human health. Pasteurization of cow’s milk protects thermolabile vitamins and other organic compounds including bioactive and bioavailable exosomes and extracellular vesicles in the range of 40–120 nm, which are pivotal mediators of cell communication via systemic transfer of specific micro-ribonucleic acids, mRNAs and regulatory proteins such as transforming growth factor-β. There is compelling evidence that human and bovine milk exosomes play a crucial role for adequate metabolic and immunological programming of the newborn infant at the beginning of extrauterine life. Milk exosomes assist in executing an anabolic, growth-promoting and immunological program confined to the postnatal period in all mammals. However, epidemiological and translational evidence presented in this review indicates that continuous exposure of humans to exosomes of pasteurized milk may confer a substantial risk for the development of chronic diseases of civilization including obesity, type 2 diabetes mellitus, osteoporosis, common cancers (prostate, breast, liver, B-cells) as well as Parkinson’s disease. Exosomes of pasteurized milk may represent new pathogens that should not reach the human food chain.